(untitled) (AmeriQuests, 2008)
Frances E. W. Harper’s Iola Leroy offers a valuable insight on the development of a holistic and natural model for patriarchy in the 19th century. Harper combines normally diametrically opposed ideologies of masculinity and femininely in the characters of Dr. Frank Latimer and Iola Leroy who become cultural heros/heroines by embracing a Black consciousness. By addressing what she considers to be a more cohesive productive society, Harper contextualizes the mulatto racial and social visions against the backdrop of the post-Reconstruction South. Within this new radical mixed race, Dr. Latimer and Iola Leroy rescues this normative stereotypical version and redefines them as the pre-cursors of Alain Locke’s “New Negro.” By rejecting whiteness as a mean to emancipate themselves out of an otherwise racial bondage, Iola Leroy and Dr. Latimer embrace the “one drop” rule. By “casting themselves” into the racial “pot,” Harper sets the mulatto up to ideally “work for the people.”